2008
DOI: 10.1111/j.1442-2042.2008.02024.x
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the urinary bladder in a patient with bilateral retinoblastoma

Abstract: Abstract:We report a case of bladder leiomyosarcoma in a 27-year-old woman who had previously been treated with surgery and radiation for bilateral retinoblastoma. The patient was admitted to hospital with discomfort on micturition. Cystoscopy revealed a bladder tumor covered by normal urothelium. Transurethral resection of the bladder tumor was performed , and the histopathological diagnosis was leiomyosarcoma. Partial cystectomy was performed. The leiomyosarcoma of the bladder did not invade the muscle layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Minogawa et al .,[ 4 ] reported a case similar to ours wherein a 27-year-old woman with bilateral retinoblastoma had been treated with surgery and radiation. They suggested that along with RB1 gene and chemotherapy, other genetic factors might also be associated with bladder leiomyosarcoma in retinoblastoma patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Minogawa et al .,[ 4 ] reported a case similar to ours wherein a 27-year-old woman with bilateral retinoblastoma had been treated with surgery and radiation. They suggested that along with RB1 gene and chemotherapy, other genetic factors might also be associated with bladder leiomyosarcoma in retinoblastoma patients.…”
Section: Discussionsupporting
confidence: 53%
“…They suggested that along with RB1 gene and chemotherapy, other genetic factors might also be associated with bladder leiomyosarcoma in retinoblastoma patients. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…Bladder leiomyoma in contrast to LMS are noninfiltrative smooth muscle tumors, lacking mitotic activity, cytologic atypia, and necrosis. [ 5 ] Other spindle cell lesions including, sarcomatoid carcinoma, inflammatory myofibroblastic tumor, and postoperative spindle cell nodule need to be distinguished from LMS. This is usually accomplished by histology and immunochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…CK expression is typically focal, if present. There are multiple cases reported as leiomyosarcoma arising in long‐term survivors of retinoblastoma, 61–67 some but not all of whom received chemotherapy (mainly cyclophosphamide). There are occasional cases in patients receiving cyclophosphamide for other conditions such as Hodgkin’s lymphoma 68,69 or lupus nephritis 70 .…”
Section: Leiomyoma Leiomyosarcoma and Sarcoma Nosmentioning
confidence: 99%